Southern oscillation and its effect on tornadic activity in the United States - Knowles, John B., author; Pielke, Roger A., Sr., author (Colorado State University. Libraries, 2005)
The Southern Oscillation has been shown in previous research to cause changes in the weather patterns over the continental United States. These changes, caused by either the warm El Nino or cold La Nina, could potentially effect numbers, locations, and strengths of tornadoes in the United States. Using a variation of the Southern Oscillation Index, the seven strongest El Nino and five strongest La Nina events during the period 1953-1989 were examined to see what effect, if any, that they would have on: 1) Total tornado numbers, 2) Violent tornado track length, 3) Violent tornado numbers, and 4) ?:40 tornado outbreaks. Little difference was found in total tornado numbers between El Nino and La Nina events. However, significant differences were found in the number of violent tornadoes, and in large number tornado outbreaks. La Nina event years were found to have longer than average track lengths, more violent tornadoes, and a good probability of having an outbreak of 40 or more tornadoes. El Nino event years were found to have shorter than average track lengths, less violent tornadoes, and only a slim possibility of having an outbreak. Possible reasons for the above conclusions include: 1) Warmer than normal temperatures in the western U.S./Canada along with cooler than normal temperatures in the southern U.S. during El Nino years; and 2) Colder than normal temperatures in the west ern U.S./Canada along with warmer than normal temperatures in the southern U.S. during La Nina years. This would act to weaken/strengthen the interactions between warm and cold air in the midwest U.S. during El Nino/La Nina event years and decrease/increase the numbers and lengths of violent tornadoes.
Published as an Atmospheric Science Paper March 31, 2005 and November 5, 1993 on title page.
Keywords: Southern oscillation; Tornadoes -- United States